STATUS ISOLEK YOGYAKARTA SURAKARTA DAN IMPLIKASINYA TERHADAP BAHASA JAWA STANDAR - suyata, pujiati; -, Suharti (LITERA, 2015)
<img src="data:image/png;base64,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